(untitled) (Revista Educação, Artes e Inclusão, 2025)
Guaranteeing access for people with disabilities is increasingly being put into practice in Higher Education. Despite the different initiatives to implement inclusion at the university level, there still remains a barrier such as the exclusionary practices of teachers. Given the above, this research aimed to investigate how teachers at a public Higher Education Institution located in the South of Minas Gerais put inclusion into practice in the classroom. For this, a methodology with a qualitative approach, of the case study type, was used. A semi-structured interview was carried out with three professors from the University’s chemistry teaching area. Then, a content analysis was carried out, where the information collected was grouped into categories. It was found that teachers do not have the pedagogical preparation to teach students with disabilities in the classroom due to gaps in their initial training and the lack of search for continued training. It is necessary to reinforce training in undergraduate courses in Brazil for an inclusive perspective, in order to prepare teachers for future work with a student with a disability and, also, to raise awareness among working teachers about the search for continued training that significantly encompasses inclusive practices and strategies.